The Influence of Self-Efficacy and Work Environment on The Work Commitment of Junior High School Teachers in Bukit Kapur Dumai District - Desmita Sari; Mahdum; Arza Ainobotika (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Teacher work commitment is a crucial factor in the success of the educational process. This commitment can be influenced by internal factors such as self-efficacy and external factors such as the work environment. This study aims to analyze the effect of self-efficacy and work environment, both partially and simultaneously, on the work commitment of public junior high school teachers in Bukit Kapur District. The research method used was quantitative with a survey approach. The sample consisted of 103 teachers selected using proportional random sampling. The research instrument was a Likert-scale questionnaire tested for validity and reliability. Data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination (Adjusted R²) after meeting classical assumption tests. The results showed that self-efficacy had a positive and significant effect on teachers’ work commitment. The work environment also had a positive and significant effect on teachers’ work commitment. Simultaneously, self- efficacy and work environment significantly influenced work commitment, contributing 43.7%, while the remainder was influenced by other factors outside the model. These findings highlight the importance of enhancing teachers’ self-efficacy and creating a conducive work environment to strengthen their work commitment.